1975
DOI: 10.2134/jeq1975.00472425000400030003x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Implications of N Fixation by Soybeans

Abstract: The objective was to measure inorganic N removal from soil by soybeans (Glycine max L.) grown at different N levels. Nodulating and non‐nodulating isolines of ‘Clark’ soybeans were planted on Flanagan silt loam in 1972 and 1973. Fertilizer rates of 0, 112, 224, and 448 kg N/ha as Ca(NO3)2 enriched with 1% 15N were applied.Symbiotically fixed N decreased from 48 to 10% of the total N in the above‐ground plant as applied fertilizer N increased from 0 to 448 kg/ha. Net removals of N by soybean grain were 61, 109,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
2

Year Published

1978
1978
2004
2004

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 0 publications
5
23
0
2
Order By: Relevance
“…This shows that plots under soybean were able to leach NO 3 -N with subsurface drainage flow as much as corn plots. A soybean crop typically accumulates 25% to 50% of its N from atmospheric N 2 fixation (Johnson et al, 1975;Harper, 1987) and uses the residual N and mineralized N from the soil for the majority of its N requirement (Olsen et al, 1970). Cambardella et al (1999) reported that substantial quantities of applied N fertilizer become incorporated in soil organic matter and remineralize in the subsequent years.…”
Section: Croppingmentioning
confidence: 99%
“…This shows that plots under soybean were able to leach NO 3 -N with subsurface drainage flow as much as corn plots. A soybean crop typically accumulates 25% to 50% of its N from atmospheric N 2 fixation (Johnson et al, 1975;Harper, 1987) and uses the residual N and mineralized N from the soil for the majority of its N requirement (Olsen et al, 1970). Cambardella et al (1999) reported that substantial quantities of applied N fertilizer become incorporated in soil organic matter and remineralize in the subsequent years.…”
Section: Croppingmentioning
confidence: 99%
“…Les conditions abiotiques de croissance des régions centrales de l'Ontario sont relativement similaires à celles des Basses Terres du Saint-Laurent. Buttery (1986), Johnson et al (1975) et Welch et al (1973) ont aussi démon-tré qu'un apport en fertilisation azotée incorporé au semis ne permettait pas d'augmenter les rendements en grains pour des soyas préalablement inoculés. L'effet de l'azote (N) est généralement non significatif sur les cinq autres variables mesurées.…”
Section: Discussionunclassified
“…Aux États-Unis, Johnson et al (1975) et Welch et al (1973) ont démontré qu'un apport en fertilisation azotée incorporé au semis n'augmentait pas les rendement en grains du soya préalablement inoculé. Lamb et al (1990) et Bhangoo et Albritton (1976) ont toutefois remar-qué que le soya pouvait répondre à la fertilisation azotée si les contenus en matière organique ou en nitrates résiduels des sols disponibles pour la plant étaient faibles ou insuffisants.…”
unclassified
“…The released N can stimulate the next crop, but it may also be leached in the interim between annual crops. The result of these differences is that even though the grain legume fixes 5 to 10 times the amount of nitrogen fixed in the cane system the grain legume tends to deplete soil fertility (Harmesen and van Schreven, 1955;Johnson et al, 1975), while soil fertility is increased under cane. Other than cane, lowland rice is possibly the only crop under which soil fertility is increased or maintained at high levels in humid tropical regions.…”
Section: Discussionmentioning
confidence: 99%